STANDARISASI DUNIA PENDIDIKAN - Subawa, Putu (Jurnal Penjaminan Mutu, 2016)
Â The educational issues that stuck out today, includes equalization of educational opportunities, quality improvement/quality, relevance and efficiency of education. Serious problems that are still felt by education from primary education to higher education is a quality problem, of course, this can be solved through technological approach to education. The use of technology in education itself has three principles that dijadiakan as a reference for the development and utilization is a systems approach, oriented to students, as well as the use of learning resources. Competence of graduates who must be the benchmark in this regard in order to form a generation of people who have the competitiveness of a competitive and innovative. The role of educators is expected to further motivate himself in each learning interaction. Transformative educators believe that students should have the ability to be actively involved in the history of the creation of man.